Assessing patient partnership among emergency departments in France: a cross-sectional study - Geoffrey Sagnol; Julie Haesebaert; Anne Termoz; Philipe Michel; Anne-Marie Schott; Véronique Potinet; Marie-Pascale Pomey; Karim Tazarourte; Marion Douplat (BMC Health Services Research, 2023)
Abstract Objectives This study aims to describe the use of patient partnership, as defined by the Montreal Model, in emergency departments (EDs) in France and report the perception of patient partnership from both the practitioner and patient perspectives. Methods This cross-sectional study was conducted between July 2020 and October 2020. First, a survey was sent to 146 heads of EDs in both teaching hospitals and non-teaching hospitals in France to assess the current practices in terms of patient partnership in service organization, research, and teaching. The perceived barriers and facilitators of the implementation of such an approach were also recorded. Then, semi-structured telephone interviews were carried out with patients involved in a service re-organization project. Results A total of 48 answers (response rate 32.9%) to the survey were received; 33.3% of respondents involved patients in projects relating to service re-organization, 20.8% involved patients in teaching projects, and 4.2% in research projects. Overall, 60.4% of the respondents were willing to involve patients in re-organization or teaching projects. The main barriers mentioned for establishing patient partnership were difficulties regarding patient recruitment and lack of time. The main advantages mentioned were the improvement in patient/caregiver relationship and new ideas to improve healthcare. When interviewed, patients mentioned the desire to improve healthcare and the necessity to involve people with different profiles and backgrounds. A too important personal commitment was the most frequently raised barrier to their engagement. All the patients recognized their positive role, and more generally, the positive role of patient engagement in service re-organization. Conclusion Although this preliminary study indicates a rather positive perception of patient partnership among heads of EDs in France and partner patients, this approach is still not widely applied in practice.